2017
DOI: 10.3390/ani7070050
|View full text |Cite
|
Sign up to set email alerts
|

Surrendered and Stray Dogs in Australia—Estimation of Numbers Entering Municipal Pounds, Shelters and Rescue Groups and Their Outcomes

Abstract: Simple SummaryAnalyses of comprehensive and accurate dog intake and outcome data in municipal pounds and shelters across states in Australia would provide an in-depth understanding of the surrendered and stray dog issue as well as facilitate effective evaluation of existing management strategies. Currently, there is a lack of comprehensive and reliable data at the federal, state and local government levels across public and private agencies. In this study, we developed a methodology to estimate the annual numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 36 publications
1
38
1
1
Order By: Relevance
“…Although it is often prohibited by municipal by-laws, some municipalities permit animal control officers to directly return stray dogs with identification to the owner, even if dog registration is not current [ 29 ]. This reduces stray admissions and is likely more cost effective for municipalities, given that some impounded dogs are not reclaimed because of cost [ 1 , 33 ]. Increasing the cost to municipal councils per dog managed by the RSPCA (and other animal welfare agencies with council contracts) may provide an incentive for municipalities to engage more proactively in increasing the number of dogs that can be returned directly to the owner.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although it is often prohibited by municipal by-laws, some municipalities permit animal control officers to directly return stray dogs with identification to the owner, even if dog registration is not current [ 29 ]. This reduces stray admissions and is likely more cost effective for municipalities, given that some impounded dogs are not reclaimed because of cost [ 1 , 33 ]. Increasing the cost to municipal councils per dog managed by the RSPCA (and other animal welfare agencies with council contracts) may provide an incentive for municipalities to engage more proactively in increasing the number of dogs that can be returned directly to the owner.…”
Section: Discussionmentioning
confidence: 99%
“…The greatest overall number of dog admissions primarily occurred in large regional centers, and 12 of the top 20 postcodes all had admissions of ≥10 dogs/1000 residents, which is above the average for Australia (9.3 dogs/1000 residents) [ 1 ]. A 2010 Australian study [ 41 ] found a significant relationship between owner demographics and pet confinement, and household income and obedience training attendance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rats, for example, are also valued human pets and, when socialised, appear to take pleasure in interactions with people [90], yet lethal control of rats is common practice. An outline of strategies to reduce stray dog populations and associated euthanasia in Australia highlighted desexing programs (low cost or free), encouragement of tagging and microchipping, and reduction of problems that contribute to surrender of owned dogs (e.g., boarding, feeding assistance, training, rental restrictions on pets)-all points that we advocate for cats-but not TNR [91]. Why should cats be treated differently?…”
Section: Reptilementioning
confidence: 99%
“…(χ²(7) = 507.4, p < 0.0001) and the estimated total dog surrenders [2] (χ²(7) = 4345.2, p < 0.0001).…”
mentioning
confidence: 99%